Detection of SARS-CoV-2 RNA in exhaled breath and its potential for prevention measures - Madiha Malik; Thomas Kunze (Elsevier, 2023)
Summary: Background: To propose infection prevention measures it is essential to understand the dynamics of SARS-CoV-2 shedding, particularly in asymptomatic patients. This report compares the viral load progression in exhaled breath (EB) with the symptom severity. We aim to evaluate the adequacy of symptom assessment regarding the infectivity level of individuals. Methods: We observed infected patients since their first positive test during hospitalization. EB samples were collected on days 1, 3, 5, 7, 10, 12 and 14 of hospitalization using a filter-based device. After extraction, viral loads were quantified with qRT-PCR. The infection trajectory was documented after symptom onset. Case Presentation and Discussion: A 34-year old patient showed mild symptoms, e.g. fever, cough, headache, muscle pain and loss of taste and smell across trajectory of infection (Case 1). The viral loads emitted via exhaling were nearly constant and ranged from 8.6 x 103 and 4.1 x 104 RNA copies per hour. After the infection, the patient developed a pneumonia. The second case of a 65-year old patient depicted an asymptomatic infection trajectory for 14 days after the first diagnosis (Case 2). Nevertheless, the patient exhaled up to 2 x 105 SARS-CoV-2 virus copies hourly, approximately 10 fold higher than measured for Case 1. Conclusion: Symptomatic and asymptomatic COVID-19 patients exhale distinctive amounts of SARS-CoV-2 not necessarily correlating with symptom severity. Particularly, asymptomatic patients might show higher EB viral shedding. Therefore, EB testing should be included in infection prevention measures as it has high potential to reveal the most infectious individuals regardless of their symptoms during infection.